Analisis Pragmatis pada Iklan Obat Batuk Herbakof - Sunardi, Ahmad; Perwitasari, Melyana (Universitas Negeri Padang, 2025)
Advertising language is very important for consumers to make choices. The presentation of advertisements, especially new product advertisements, must be able to choose the right words, attractive advertising stars, and clear information. This study aims to analyze the text of Herbakof cough medicine advertisements. The analysis method used includes various aspects, such as the main message, pragmatic techniques, visual and auditory elements, target audience, and celebrity appeal. The results of the study are in the form of illocutionary speech acts, loci and perlocution. Implicature is found in the taste of